SOSIALISASI CARA MENCUCI TANGAN SESUAI PROTOKOL KESEHATAN MELALUI MEDIA SOSIAL - SHODIKIN,; DWI KRISTIANI, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2021)
The world is currently being hit by disease outbreak, namely Corona Virus Disease 19 or commonly abbreviated as Covid-19. This virus was first discovered in Wuhan in late December 2019. The spread of the virus was so massive and difficult to control that the government declared that this was a pandemic that had to be seriously resolved. One of the preventions that people can do is by washing their hands cleanly. Hand washing has indeed been one of the government programs that have been campaigned for a long time. However, with this incident, washing hands is one of the most important ways to break the Covid-19 chain. This habit must be done from an early age because it is easier for children at the golden age to impart knowledge which of course can be done in everyday life. For this reason, we selected videos to socialize this hand washing movement so that children are easy to understand and imitate. In the video, there is a song that you can sing, making it easier to memorize the steps. The show also uses a model of children practicing hand washing so We hope that it will be easier to remember and imitate.